Pengaruh Self-Efficacy, Adversity Quotient, dan Dukungan Sosial Terhadap Kinerja Pelaku Usaha UMK Laguna Surabaya - Dini Septiningtyas; Awin Mulyati; Ute Chairuz M. Nasution (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Because in today's tight business competition, business actors must have good performance in managing their business. This study uses a quantitative approach. The sample in this research was the MSE business actors in Laguna Surabaya. The number of samples in this study was 50 respondents. The sampling technique used is non-probability sampling, with the method used being saturated sampling. The data analysis used in this research is the t test and F test. The results of this research show that the partial analysis test of the F test analysis in this research shows that Self-Efficacy, Adversity Quotient and Social Support have a significant effect together (simultaneously) on Actor Performance. Laguna Surabaya MSE Business. Thus, it can be said that the three variables, namely Self-Efficacy, Adversity Quotient and Social Support, simultaneously and partially have a significant influence on the Performance of Business Actors. The Self-Efficacy variable is the most dominant variable. on the Performance of Business Actors. Business actors are expected to increase their self-confidence in the business sector they are involved in, business actors must pay attention to themselves in controlling their emotions and the cooperation carried out by the business community with government institutions can help business actors.